Squamous cell carcinoma antigen (SCC) in diagnostics and monitoring treatment of patients with cervical cancer - Stępień, Marcin; Kornafel, Jan (Contemporary Oncology/Współczesna Onkologia, 2006)
Squamous cell carcinoma antigen (SCC) is the first marker of squamous cell carcinoma and a member of the serin proteinase inhibitor family. Increased concentration of SCC occurs in squamous cancers of the region of the head and neck, oesophagus, larynx, neck of the uterus, and oral cavity. SCC is not a specific marker of squamous cancer. Its increased concentration is noted also in certain cancers and non-cancer diseases. Many scientists have shown the suitability of antigen SCC in assessment of early effects of squamous cancer treatment. In our study we showed the suitability of antigen SCC in diagnostics and monitoring of treatment for patients suffering from cervical squamous cell carcinoma. Together with growth of the degree of clinical advancement, concentration of antigen SCC in the patient’s blood increases. There is a dependency between concentration of antigen SCC before commencement of treatment and further assessment of early and later results of the treatment for patients suffering from cervical squamous cell carcinoma. Concentration of antigen SCC was analysed for 163 patients suffering from cervical squamous cell carcinoma in various degrees of clinical advancement. 118 of them were subject to 5- and 10-year observation after the completed radical treatment. In addition, sensitivity of antigen SCC determinations depending on the degree of clinical advancement was assessed. Results of the analysis indicate a correlation of antigen SCC concentration with the degree of clinical advancement of the disease. Suitability of the marker in monitoring of treatment effects for patients suffering from cervical squamous cell carcinoma was also proved. Thirdly, the dependence of prognosis for patients suffering from cervical squamous cell carcinoma on initial concentration of SCC in the blood before commencement of treatment was shown.